2021
DOI: 10.1016/j.apacoust.2021.108200
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of long acoustic waveguides for the very low frequency characterization of monolayer and stratified air-saturated poroelastic materials

Abstract: When sound propagates in a porous medium, it is attenuated via several energy loss mechanisms which are switched on or o as the excitation frequency varies. The classical way of measuring acoustic energy loss in porous materials uses the Kundt impedance tube. However, due to its short length, measurements are made in the steady state harmonic regimes. Its lower cuto frequency is often limited to a few hundreds of Hertz.Two long acoustic waveguides were assembled from water pipes and mounted to create test-rigs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The amplitudes and velocities of the transmitted longitudinal waves (slow and fast) are observed and compared in order to see the impact of taking into account the shear wave in the model. In our previous work [19,62], we did not take into account the shear wave at normal incidence, but recent studies [62,67] have shown that the shear wave must be taken into account because of the viscous exchanges between fluid and structure. At normal incidence, the shear wave is not as visible as the fast and slow longitudinal waves because its amplitude is very low; however, its effect is felt in the amplitudes and speeds of longitudinal waves, and this effect varies depending on the values of the physical parameters of the porous medium, as shown in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amplitudes and velocities of the transmitted longitudinal waves (slow and fast) are observed and compared in order to see the impact of taking into account the shear wave in the model. In our previous work [19,62], we did not take into account the shear wave at normal incidence, but recent studies [62,67] have shown that the shear wave must be taken into account because of the viscous exchanges between fluid and structure. At normal incidence, the shear wave is not as visible as the fast and slow longitudinal waves because its amplitude is very low; however, its effect is felt in the amplitudes and speeds of longitudinal waves, and this effect varies depending on the values of the physical parameters of the porous medium, as shown in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In order to test the validity of our analytical development and to show the influence that the shear waves can have on the response of bone-type porous materials, we proceed to compare transmitted signals obtained during this study, the shear waves being taken into account, and the transmitted signals, where only the longitudinal waves are observed because the shear waves are very weak in normal incidence; however, whether or not they are taken into account is visible on the longitudinal waveforms, as shown in the following study. The characteristics of the bone samples used in this study were taken from work carried out previously by Fellah [67] and are shown in Table 1. The transmitted signals are computed by performing the convolution product of the transmission operator given by (45) with the incident signal, as in the relation in (33).…”
Section: Numerical Validationmentioning
confidence: 99%
“…The prepared CEBs samples, which were further characterised, were designed to perfectly fit into a segment of an 18.0 m long pipe (acoustic waveguide) with an internal diameter of 76.2 mm (3.00 inch), which was made up of three polyurethane water pipes connected together. The frequency range of the pipe (18.8 to 2621.6 Hz) was determined from the Formula (1) [39]:…”
Section: Measurementsmentioning
confidence: 99%
“…In this section, we show how the results developed so far may be applied to specific situations. We consider the example of two acoustic waveguides coupled by an interface consisting in some membrane which acts as a local acoustic impedance as it appears, for instance, in [21].…”
Section: Then the Following Assertions Are Equivalentmentioning
confidence: 99%